Kaina ka palaia: sacred contemplations, in three parts ... - Gib, Adam (Printed by W. Young and J. M'Culloch, 1788)
1. A view of the covenant of works -- 2. A view of the covenant of grace -- 3. A view of the absolute and immediate dependence of all things of God.